Photoelectrocatalytic degradation of methylene blue on cadmium sulfide–sensitized titanium dioxide film. (October 2019) - Wu, Yu-Hsuan; Wu, Tsunghsueh; Lin, Yang-Wei
Graphical abstract: CdS enhanced photoelectrocatalytic activity of TiO2 films under sunlight irradiation. Highlights: Report 6-CdS/TiO2 -film photoelectrocatalytic degradation (PEC) of methylene blue. Elucidate PEC degradation mechanism of 6-CdS/TiO2 . Evaluate factors causing PEC methylene blue degradation in complex matrix. Abstract: Herein, cadmium sulfide–sensitized titanium dioxide (CdS/TiO2 ) deposited on a fluoride-doped tin oxide electrode is proposed for achieving the photoelectrocatalytic (PEC) degradation of methylene blue (MB). Under optimum conditions (six accumulative CdS depositions, 3.0-V DC applied biased potential, and 300-W Xe arc lamp irradiation), the prepared CdS/TiO2 films exhibited the highest PEC degradation of MB (82 ± 3%) compared with photocatalytic (70 ± 5%) or electrocatalytic (39 ± 5%) degradation. In addition, the higher current density (0.08425 mA/cm 2 ) and the lower charge transfer resistance (78.5  Ω) of 6-CdS/TiO2 film were observed. These were attributable to the strong visible light absorption of CdS, the high charge separation efficiency in the CdS/TiO2 heterostructure, and the low electron–hole recombination rate from the applied biased potential. The feasibility of 6-CdS/TiO2 film was evaluated by the MB degradation in environmental water samples, which demonstrated a high PEC activity (71 ± 3% degradation) of CdS/TiO2 film.